(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Salmonellosis is an acute infectious disease caused by bacteria belonging to the genus Salmonella, transmitted by the fecal-oral mechanism, and mainly caused by damage to the gastrointestinal tract.